The effect of overtime work, work-life balance, and work environment on employee performance - Radatta, Ni Putu Heda; Supartha, Anak Agung Ayu Rika Putri (Universitas Pendidikan Nasional, 2022)
Human resources are the heart of a company because they have an important role in the success of achieving the vision, goals, and mission that have been inaugurated. Success depends on employees performing their job obligations. This proves that companies must have management related to human resource management, where the company's mission and employees can succeed in an active way. Human resources as the main asset in driving a company or organization, in its mission the company is required to develop the quality of its human resources so that it can remain competitive with other competitors plus technological developments that have a very big influence in the changing times today. Improving employee performance should be noticed in several aspects such as Overtime, Work-Life Balance, and Work Environment. CV Akemi Bali Craft is a company or industry that produces handicrafts and household items made of wood. Its address is in Beneng Village, Getakan, Banjarangkan District, Klungkung, Bali. The majority of production results are exported abroad such as Japan. Mostly their employees got more overtime to finish target production, so it’s caused underperform from the employees. This study used a quantitative method by distributing questionnaires to respondents, namely CV Akemi Bali Craft employees, a total of 113 employees. The results showed that over time has a negative and important influence on employee performance, work-life balance has a positive and important influence on employee performance, Work Environment has a positive and important influence on employee performance, and over time, work-life balance, and work environment have a positive and important influence on employee performance.